Design and Comprehensive Simulation of 5 MWp and 10 MWp Solar Power Plants in Ma'an: Detailed System Design, Economic Returns, and Environmental Benefits in a Semi-Arid Climate - İbrahim Mahmoud Rizeq Alsaqar; Mehmet Erdem (Gazi Üniversitesi Fen Bilimleri Dergisi)
The energy sector in Jordan is facing major challenges due to the increasing demand for elec-tricity and limited oil resources, which calls for the search for sustainable solutions. This study aims to present a comprehensive design of a solar power plant, starting with site selection in Ma'an, Jordan, where a careful analysis of solar radiation and environmental conditions was per-formed to ensure efficient production. The optimal tilt angle of the solar panels was determined at 30 degrees to maximize the absorption of solar radiation and improve system efficiency. In addition, a scientific methodology was applied to select the appropriate electrical cables, ensur-ing the minimization of electrical losses and achieving the highest level of operational efficiency. On the economic level, a comprehensive financial analysis was conducted to assess the invest-ment feasibility of the project, where the results showed that the plant achieves high investment returns and a short payback period, which enhances the feasibility of investing in solar energy projects. Moreover, the amount of GHG emission reduction achieved by the plant was calculat-ed, highlighting its effective role in reducing the carbon footprint and promoting environmental sustainability. This study reflects the importance of investing in solar energy projects, especially in semi-arid regions with high solar radiation, as they provide effective solutions to achieve en-ergy sustainability and reduce dependence on fossil fuels.